The Development of Internalization of Character Responsibility Through the Cooperative Learning Model on Students in Elementary School - Widita, Anindya; Nurihsan, Ahmad Juntika (International Conference on Elementary Education, 2020)
The crisis of the degradation of the character that occurs today is very worrying, especially the character of responsibility in elementary school students. Given the age of elementary school students (children) is the golden period of development which determines the basic personality of rice a person, then the character of responsibility early on need to be implanted. If the character of responsibility instilled since childhood, then later as an adult will be able to carry out various forms of responsibility that became his duty either to themselves, society, environment, nation and Country as well as on his Lord. Character responsibility can be internalized by way of direct learning with an innovative learning model by giving the task so that it can enhance the affective aspect of character in the form of the responsibility of the student. One of learning model that is expected to form the character of responsibility is a model of cooperative learning. This scientific work aims to determine the planting internalization of character responsibility through the model of cooperative learning on elementary school students. Literature review is the method used in this paper. Cooperative learning Model will be a contribution to the character of the responsibility of elementary school students